2003
DOI: 10.1046/j.1432-1033.2003.03728.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of enzyme acylation and deacylation in the penicillin acylase‐catalyzed synthesis of β‐lactam antibiotics

Abstract: Penicillin acylase catalyses the hydrolysis and synthesis of semisynthetic b-lactam antibiotics via formation of a covalent acyl-enzyme intermediate. The kinetic and mechanistic aspects of these reactions were studied. Stopped-flow experiments with the penicillin and ampicillin analogues 2-nitro-5-phenylacetoxy-benzoic acid (NIPAOB) and D-2-nitro-5-[(phenylglycyl)amino]-benzoic acid (NIPGB) showed that the rate-limiting step in the conversion of penicillin G and ampicillin is the formation of the acylenzyme.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 37 publications
2
24
0
2
Order By: Relevance
“…The active site is at the bottom of a conic depression formed by residues of the two sub-units, which are tightly intertwined. The crystal structure of the enzyme complexed with different side chain ligands has been reported in different papers [33,[35][36][37][38][39].…”
Section: Pgamentioning
confidence: 99%
“…The active site is at the bottom of a conic depression formed by residues of the two sub-units, which are tightly intertwined. The crystal structure of the enzyme complexed with different side chain ligands has been reported in different papers [33,[35][36][37][38][39].…”
Section: Pgamentioning
confidence: 99%
“…In the past year a kinetic analysis of the penicillin reaction steps was published with emphasis not only on the hydrolysis reaction, but also on the synthetic reaction [32]. The acylation step and the deacylation step have been described as separate steps in the reaction and it was shown that the breakdown of the acyl-enzyme is much faster than its formation, implying that the rate of hydrolysis is set entirely by the acylation step.…”
Section: Mechanism Of the Acylase Reactionmentioning
confidence: 99%
“…However, the subtle differences in the structure of the enzyme and enzyme-substrate interactions in the active site can strongly affect the energetics of the reaction and have a major impact on the efficiency of catalysis [1,13,14]. Penicillin G acylase from Alcaligenes faecalis (Af-PGA) is structurally very similar to the Escherichia coli enzyme (Ec-PGA) [11].…”
Section: Introductionmentioning
confidence: 99%